An implementation of Geographic Information System (GIS) for online classroom reservation (GISClaR) / Ahmad Subhi Zolkafly - Zolkafly, Ahmad Subhi (2013)
Conventional reservation systems have a lot of problems such as class clashing, missing of reservation data and bureaucracy that faced by the user. In addition, user also difficult to find the coordination of the classroom because the conventional system did not provide any floor plan image to the user. Multitasking user nowadays prefer to use internet for ease their daily life. Therefore, the conventional system became not relevant or not popular. In order to solve these problems, an implementation of Geographic Information System (GIS) for online classroom reservation had been developed. This reservation system implemented GIS to provide a classroom floor plan image for the user. The implementation of GIS provides additional information about classroom. The uses of clashing algorithm also solve the class clashing problems. The online classroom system makes user daily life easier than conventional system. Users do not have to facing bureaucracy and easy to book a classroom anywhere and anytime.